2015
DOI: 10.3390/ma8063633
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Membrane Reactor for the Removal of C.I. Disperse Red 73

Abstract: After the dyeing process, part of the dyes used to color textile materials are not fixed into the substrate and are discharged into wastewater as residual dyes. In this study, a heterogeneous photocatalytic process combined with microfiltration has been investigated for the removal of C.I. Disperse Red 73 from synthetic textile effluents. The titanium dioxide (TiO2) Aeroxide P25 was selected as photocatalyst. The photocatalytic treatment achieved between 60% and 90% of dye degradation and up to 98% chemical ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Many authors reported the importance to maintain the photocatalytic reactions below the catalyst's point of zero charge (PZC) (Chong et al, 2010). The literature values of pH PZC for Aeroxide TiO 2 P25 range from 6.5 to 6.7 (Boncagni et al, 2009;Buscio et al, 2015;Kritikos et al, 2007). However, pH PZC values of FeZ and pristine NH 4 ZSM5 are found to be 2.37 and 2.81, respectively (Juretic Perisic et al, 2016).…”
Section: Influence Of Process Parameters On Effectiveness Of Solar/timentioning
confidence: 92%
“…Many authors reported the importance to maintain the photocatalytic reactions below the catalyst's point of zero charge (PZC) (Chong et al, 2010). The literature values of pH PZC for Aeroxide TiO 2 P25 range from 6.5 to 6.7 (Boncagni et al, 2009;Buscio et al, 2015;Kritikos et al, 2007). However, pH PZC values of FeZ and pristine NH 4 ZSM5 are found to be 2.37 and 2.81, respectively (Juretic Perisic et al, 2016).…”
Section: Influence Of Process Parameters On Effectiveness Of Solar/timentioning
confidence: 92%
“…For this reason, a rising interest occurs on supported nanomaterials. In seek of always increasing the exposed specific surface area of nanotextured photocatalysts, their synthesis at the surface of porous support like membranes has been envisaged for water treatment [18,19] or water splitting [20,21]. Currently, membranes are mainly studied for the photocatalytic water treatment as they combine the double advantages of filtration, and photocatalytic degradation of water pollutants (hybrid filtration/photocatalytic membranes).…”
Section: Nanostructured Supported Photocatalystsmentioning
confidence: 99%
“…Buscio et al [76] studied removal of red dye using flow-through photo-catalytic membrane, where titanium dioxide was the loaded catalyst and the degradation of dye by oxygen reached to 87 % at 50 ppm of red dye [76]. Also, Li et al [77] prepared sand-wished nanofiber photocatalytic membrane made from three layers upper and lower layer of polymethylmethacrylate (PMMA) and H4SiW12O40 blended nanofibers, while the middle layer was polyvinyl alcohol (PVA), the membranes were prepared by electrospinning technique, the photooxidative degradation of azo-dyes was studied and the membrane provided 72.9 % within 30 min degradation of the organic dye [77].…”
Section: Photocatalytic Reactionsmentioning
confidence: 99%